On the suitability of offshore wind energy resource in the United States of America for the 21st century. (15th March 2020) - Costoya, X.; deCastro, M.; Carvalho, D.; Gómez-Gesteira, M.
Graphical abstract: Highlights: Impact of climate change on offshore wind energy is relevant in the decision making. Regional models properly reproduce offshore wind on the United States coasts. A decrease of the offshore wind resource is projected along the 21st century. The central area of both coasts was classified as excellent (present and future) A slight decrease is projected in the wind energy classification for the east coast. Abstract: Despite the United States of America offshore wind energy sector is currently ramping up in terms of offshore wind farms projects and investment, installed offshore wind farms are yet scarce in the country (30 MW currently installed). Therefore, it is necessary to analyze the current offshore wind energy resource and the projected future variations since an important development is expected in the next decade for the United States offshore wind energy sector. With this aim, simulations from 12 Regional Climate Models from North America Coordinated Regional Climate Downscalling Experiment were used after proving its reliability by comparing the wind speed from simulations with in-situ data. A decrease of the offshore wind energy resource is projected along the 21st century in the United States, especially in the east coast. The central west coast is the only exception to this decrease trend during the near and mid future. In addition, the offshore wind energy resource was classified following a Delphi approach and considering three factors: wind energy, environmental risk and costs. Under this classification, most of the area under scope in both coasts was classified at least as a 4, which is considered as "good" resource. A higher wind energy resource was found for the west coast, with vast coastal areas categorized as 5 ("excellent"). A slight decrease was projected on the United States east coast, mainly caused by a reduction in the indices related to the mean wind speed and the stability of the resource throughout the year.